Varieties of economization in competition policy: A comparative analysis of German and American antitrust doctrines, 1960-2000 - Timur Ergen; Sebastian Kohl (Max Planck Institute for the Study of Societies, 2017)
This paper explains the different trajectories of German and American competition policy and its permissiveness towards economic concentration in the last few decades. While the German political economy had moved to a stronger antitrust regime after 1945 and stuck to it even after the economic governance shifts of the 1980s, the traditional antitrust champion, the United States, has shed considerable parts of its basic governance toolkit against anticompetitive conduct since the 1960s. Drawing on theories of institutional change driven by bureaucratic and professional elites, the paper claims that different pathways of professional ideas in competition policy can account for the cross-country differences. In the 1960s and early 1970s, movements to strengthen competition policy in the direction of an active deconcentration of industry emerged in both countries. While German as well as American professionals reacted to the impending encroachment of societal concerns into antitrust with economized notions of the policies' goals, they did so in fundamentally different ways. Whereas US professionals proposed an effect-based approach in which consumer welfare and gains in efficiency may justify less competition, the more strongly law-based profession in Germany to a degree strengthened a form-based approach aiming at the preservation of competitive market structures. Such extrapolitical pathways of ideas, we argue, provide important guidelines for the implementation of competition policy by administrations and courts, whose decisions can have a far-reaching impact on industries and political economies as a whole. – – Der Artikel erklärt die unterschiedlichen Pfade des deutschen und amerikanischen Wettbewerbsrechts und dessen Einstellung zu wirtschaftlicher Konzentration in den letzten Jahrzehnten. Während die deutsche politische Ökonomie nach 1945 zu einem konservativeren Wettbewerbsregime überging und dies auch nach dem Wandel in den 1980er-Jahren aufrechterhielt, veränderten die USA, das klassische Land der Wettbewerbskontrolle, ihr Interventionsverhalten seit den 1960er-Jahren. Dieser Artikel argumentiert mit Bezug auf Theorien institutionellen Wandels durch bürokratische Eliten, dass die verschiedenartigen Wettbewerbsideen von Professionen die Länderunterschiede miterklären können. In den 1960er- und 1970er-Jahren entstanden in beiden Ländern Bewegungen, die das Ziel verfolgten, Wettbewerbspolitik zu erweitern. Wenngleich sowohl deutsche als auch amerikanische professionelle Gruppen auf das drohende Vordringen gesamtgesellschaftlicher Erwägungen mit ökonomisierten Auffassungen der Wettbewerbspolitik reagierten, taten sie das in unterschiedlicher Weise. Während amerikanische professionelle Gruppen einen effektbasierten Ansatz entwickelten, in dem Konsumentenwohlfahrts- und Effizienzgewinne Abstriche beim Wettbewerb erlauben, stärkten die eher juristisch geprägten Wettbewerbshüter in Deutschland einen marktformbasierten Ansatz. Wir behaupten, dass diese verschiedenen Ideen wichtige Leitlinien in der Implementierung des Wettbewerbsrechts für Verwaltungen und Gerichte vorgaben, deren Entscheidungen wiederum weitreichende Effekte für Wirtschaftssektoren und die politische Ökonomie insgesamt haben können.
hdl:11858/00-001M-0000-002E-0187-B
Keywords: 300; competition; law; economization; professions; ideas; Wettbewerb; Recht; Ökonomisierung; Professionen; Ideen